Criminal Law System Against Illegal Logging in Law No. 18 of 2013 concerning Prevention and Eradication of Forest Destruction - Wijayanto, Indung (Law Research Review Quarterly, 2015)
Forests have an important function for Indonesia even for other countries. Considering the importance of forests, forests need to be preserved one of them is to provide legal protection in the form of laws. UU no. 41 of 1999 concerning Forestry is no longer felt capable of overcoming the illegal logging crime which has been growing from year to year, both in terms of car and its shape. In 2013, Law No. 18 of 2013 to respond to various developments so that the handling of illegal logging is more effective. Keywords: Illegal Logging, Criminal System